Supercritical deformations - Cherepanov, G.P. (Проблемы прочности, 1985)
The basic conclusion of the work may be formulated in the following manner. Supercritical deformations of solids within the limits of the theory of infinitely small deformations are always concentrated in infinitely narrow zones simulated by surfaces of discontinuity of the displacements.